2017
DOI: 10.1515/bjdm-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings in cone-beam computed tomographic images: Calcifications in head and neck region

Abstract: Summary Background/Aim: The use of CBCT in dentistry has been increasing popularity nowadays. CBCT images provide valuable information from anatomic structures and pathologies. Images obtained with CBCT allow for more appropriate treatment planning. The purpose of this study was to assess the calcifications which were found incidentally on CBCT images and to reveal the frequency and characteristics. Material and Methods: A total of 691 CBCT images which obtained from the patients were assessed. Demographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…They can also occur in minor salivary glands, primarily in the upper lip and buccal mucosa. According to literature, incidences of sialoliths are low, between 0.2% and 1.01% [81,82].…”
Section: Sialolithmentioning
confidence: 99%
See 3 more Smart Citations
“…They can also occur in minor salivary glands, primarily in the upper lip and buccal mucosa. According to literature, incidences of sialoliths are low, between 0.2% and 1.01% [81,82].…”
Section: Sialolithmentioning
confidence: 99%
“…The most common sites include the pineal gland, habenula, choroid plexus, basal ganglia, falx, tentorium, petroclinoid ligaments, and sagittal sinus [111]. According to the literature, intracranial calcifications were common and occur at any age and of any ethnicity [81]. Kwak et al [112] reported that intracranial calcifications have male predilection.…”
Section: Intracranial Calcificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of the CBCT scanner contributed to a significant reduction in the scanning time, radiation dose, costs, and also the possibility of its use in dental clinics as a standard equipment. CBCT scanners can be used in various diagnostic procedures in dentistry, providing precise diagnostic data not only in the region of interest, but also in the surrounding structures 10 . Soardi et al 11 also stated that there is no statistically significant difference in determining bone tissue density between microradiography or CBCT devices.…”
Section: Introductionmentioning
confidence: 99%